Research on Evaluation of Higher Vocational English Teaching for Cruise Stewarding Management Majors Based on OBE Concept - Hu, Xiaoli; Hu, Honghua (Journal of Social Science and Humanities, 2025)
In the context of the rapidly developing global cruise tourism industry, there is a growing demand for cruise stewarding management professionals with proficient English communication skills. Traditional evaluation methods for higher vocational English teaching often focus on knowledge assessment, failing to fully reflect or foster the practical language application abilities required by the industry. This paper explores the construction and implementation of a teaching evaluation system for Cruise Stewarding Management majors based on the Outcomes-Based Education (OBE) concept. It analyzes the applicability of OBE’s core principles—outcome focus, reverse design, personalized instruction, and continuous improvement—to the practical, culturally diverse, and highly operational nature of English teaching in this field. It details the process of defining evaluation objectives and standards centered on specific vocational competencies and cross-cultural communication skills. Furthermore, this paper advocates for utilizing diverse evaluation methods and tools, integrating formative and summative assessments alongside digital platforms, to comprehensively gauge student learning outcomes. While the implementation of this OBE-based evaluation system demonstrates positive effects on student motivation, oral proficiency, and cross-cultural skills, the study also identifies challenges, including insufficiently precise evaluation standards and a lack of methodological diversity. Corresponding improvement strategies are proposed, such as involving industry professionals in standard refinement and incorporating more project-based assessments. This paper concludes that an OBE-oriented evaluation system holds significant promise for enhancing teaching quality, aligning educational outcomes with industry needs, and offers valuable insights for English teaching reform in related vocational fields.